IMPLEMENTATION OF THE TARL APPROACH TO INCREASE LEARNING MOTIVATION IN PJOK LEARNING - Firmansyah, Erlan; Herlambang, Tubagus (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2024)
This research is research that aims to increase students' learning motivation in PJOK learning using or implementing the TaRL (Taching at the Right Level) approach. This type of research is classroom action research (PTK). The subjects of this research used 1 class of Class X SMK students totaling 37 students at SMKN 8 Semarang. Classroom Action Research by conducting observations and distributing student learning motivation questionnaires in PJOK learning. The results of this research show that as many as 68% of students feel happy when taking part in PJOK learning with the implementation of the TaRL (Taching at the Right Level) approach because they are grouped according to their respective ability levels and students like learning by collaborating with their group in solving tasks or problems. The research that has been conducted shows that the TaRL approach can increase students' learning motivation.